2012
DOI: 10.1128/jvi.00534-12
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Bite Delivery of Dengue Virus Enhances Immunogenicity and Pathogenesis in Humanized Mice

Abstract: bDengue viruses (DENV) are transmitted to humans by the bite of Aedes aegypti or Aedes albopictus mosquitoes, with millions of infections annually in over 100 countries. The diseases they produce, which occur exclusively in humans, are dengue fever (DF) and dengue hemorrhagic fever (DHF). We previously developed a humanized mouse model of DF in which mice transplanted with human hematopoietic stem cells produced signs of DENV disease after injection with low-passage, wild-type isolates. Using these mice, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(222 citation statements)
references
References 62 publications
8
205
0
2
Order By: Relevance
“…immune hemolytic anemia, immune thrombocytopenia (Gupta 2013;Cox 2012), and even cancer, which are life-threatening conditions if appropriate treatments are not soon issued (Kristinsson 2013;Hull 1988). et al, et al, et al, et al, …”
Section: Resultsmentioning
confidence: 99%
“…immune hemolytic anemia, immune thrombocytopenia (Gupta 2013;Cox 2012), and even cancer, which are life-threatening conditions if appropriate treatments are not soon issued (Kristinsson 2013;Hull 1988). et al, et al, et al, et al, …”
Section: Resultsmentioning
confidence: 99%
“…It is well established that mosquito transmission can affect arbovirus infection outcomes, but 237 outcomes vary depending on the mosquito-virus-host system 11,12,17,35 . In this study we found a 238 single sc dose of 1 x 10 4 PFU of ZIKV led to similar tissue distribution as observed in mosquito-239 inoculated animals at 15 dpi.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is Thementioning
confidence: 99%
“…Subcutaneous inoculation, 264 by contrast, likely resulted in slower dissemination through the draining lymph nodes; 265 dissemination may be slower still following mosquito infection, as indicated by the delay in peak 266 viral loads observed with mosquito-bite delivery of virus in this study. In addition, the use of 267 multiple simultaneous injections 36 could iatrogenically cause disease signs 17 . For example, the 268 fever response observed with multiple injections might be expected, given that injection of virus 269 stocks also delivers cell culture medium components that might serve as irritants; needle 270 puncture of the skin is also more traumatic than insertion of a mosquito proboscis.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is Thementioning
confidence: 99%
See 1 more Smart Citation
“…The low dose ID route produced a higher percentage of tetravalent antibody seroconversion rates by PRNT compared to the high dose SQ route (71 % vs. 47 %) [42,43]. It is possible ID dosing more closely resembles mosquito delivery of virus, resulting in more efficient antigen processing, and therefore superior immunogenicity [44]. The majority (83 %) of subjects had detectable DENV-2 viral RNA after the first dose, but none had detectable viral RNA after the second dose [42].…”
Section: Chimeric Yellow Fever Dengue (Cyd) Tetravalent Vaccine-sanofmentioning
confidence: 99%